Activin A improves the outcomes of neurological function in mice with ischemic stroke through ACVR1C of oligodendrocytes - LI Yudie, WANG Hongyu, HAN Song, LI Junfa (Jichu yixue yu linchuang, 2023)
Objective The role of activin A receptor type 1C(ACVR1C) in white matter remyelination and neurological outcome of mice with ischemic stroke were investigated. Methods Mice were randomly divided into empty virus vector sham operation group, adeno-associated virus(AAV) sham operation group, empty virus vector model group, AAV model group, empty virus vector activin group A and AAV activin group A.Acvr1cflox/flox mice with middle cerebral artery oclusion-reperfusion (MCAO/R) for 1 to 10 days were established. Adeno-associated virus AAV-PDGFRα-cre and AAV-PLP-cre with cre recombinase were injected into the lateral ventricles of the mice. Conditional knockout of Acvr1c on oligodendrocytes and oligodendrocytes. Neurological function score was used to observe the prognosis of neurological function. The expressions of ACVR1C protein and myelin basic protein (MBP) were detected by Western blot. Results With the extension of reperfusion time, activin A improved the behavioral outcome of mice by ACVR1C on oligodendrocytes at day 7 (P＜0.05), and significantly increased the expression of MBP protein in corpus callosum at day 10 (P＜0.05). Conclusions Activin A promotes white matter remyelination and improves outcomes of neurological function of ischemic stroke mice by acting on ACVR1C on oligodendrocytes.